Realistic Mathematics Education (RME) untuk Meningkatkan Kemampuan Pemecahan Masalah Matematis Siswa di Indonesia - I Wayan Widana (Jurnal Elemen, 2021)
Problem-solving ability in the real world is the main competency that students must possess in the 21st century. RME can bridge abstract mathematical concepts obtained in the classroom with the real world. This research is a meta-analytic study aimed at analyzing the effect of the RME learning model on problem-solving abilities. The data was obtained from a search of scientific articles that have been published in Science and Technology Index (SINTA) 2, 3, and 4 accredited journals and national proceedings in the period 2016-2021 and is an experimental study with a non-equivalent pre-test and post-test control group design. The research samples that matched the exclusion and inclusion criteria were seven units. The data were analyzed using the JASP V-0.11 application. The results of the heterogeneity test with a value of Q=10.277 and p=0.1130.05. The combined effect size model used is the fixed effect model. The results showed that the average effect size was 0.42 in the medium effect category. The Funnel Plot and Egger's Test tests with a value of z=0.075 and p=0.9400.05 indicated no publication bias. In conclusion, the RME learning model affects students' mathematical problem-solving abilities with moderate influence. The results of this study contribute to strengthening the findings of previous studies.